2019
DOI: 10.2147/prbm.s198443
|View full text |Cite
|
Sign up to set email alerts
|

<p>The mediating role of psychological capital on the association between workplace violence and professional identity among Chinese doctors: a cross-sectional study</p>

Abstract: Background: Workplace violence (WPV) and psychological capital (PsyCap) are linked to professional identity, however, little research has examined how WPV is associated with professional identity via PsyCap. This study is aimed to examine the association between WPV and professional identity, and to further explore whether PsyCap can serve as a mediator between WPV and professional identity among Chinese doctors. Materials and methods: A cross-sectional study was conducted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 35 publications
5
34
0
Order By: Relevance
“…In agreement with this, a study in China demonstrated that hope was significantly associated with the professional identity. 55 On the same line, a qualitative study on Greek nurses revealed that the way nurses perceive themselves from the personal as well as the professional aspects, i.e., their professional identity, does influence their wellness feelings. 56…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, a study in China demonstrated that hope was significantly associated with the professional identity. 55 On the same line, a qualitative study on Greek nurses revealed that the way nurses perceive themselves from the personal as well as the professional aspects, i.e., their professional identity, does influence their wellness feelings. 56…”
Section: Discussionmentioning
confidence: 99%
“…Psychological capital can maintain one's ambition to accomplish goals and boost the positive psychological ability to deal with difficult problems (52,53). Other researchers are also concerned about the potential role of PsyCap among doctors (33,54,55). Qiu et al (33) showed workplace violence will reduce doctors' PsyCap level, as well as result in low-level professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of many previous studies, a vital notion derived from organizational psychological behavior is psychological capital (PsyCap). It is a positive resource and psychological force against "doctor pressure and resignation" (29)(30)(31)(32)(33). As an exploitable human resource, PsyCap can be suitably developed through training and intervention programs (34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional identity means that an individual understands the influence of his occupation in society and the importance of his work, which is the psychological foundation for the effective implementation of work and the realization of organisational goals (Zhang et al., 2018). The development of professional identity is attributable to the internalization of knowledge, skills, attitudes, professional values and moral standards, which are then integrated into personal identity and behaviour in nursing education and practice (Cowin et al., 2013; Qiu et al., 2019). People with a strong professional identity are often proud of their professions and achieve growth and self‐realization through their professions, and such a strong professional identity is strongly associated with subjective well‐being (Jue & Ha, 2018).…”
Section: Introductionmentioning
confidence: 99%